Performance and mechanism of waste engine oil in the regeneration of aged asphalt from different perspectives - Yi Wang; Jin Wang; Wei Cui; Hongwei Wang; Fan Zhang; Fayong Yang (PLoS ONE, 2025)
To expand the utilization pathways of waste engine oil (WEO) and address the issues arising from road aging, this study investigates the regeneration effect of WEO as a rejuvenator for aged asphalt. The performance degradation of asphalt under different aging durations was analyzed, and a predictive model correlating aging time with performance decline was developed. Then, the influence of different dosages of WEO on the regeneration of aged asphalt was examined, and the regenerative mechanism in aged asphalt was explored through microscopic analysis. Furthermore, the molecular simulation was employed to elucidate the molecular-level interactions between the rejuvenator and aged asphalt. The results showed that as aging time increases, the rotational viscosity at 135°C increases with aging time, rising by 8.9% to 40.9%, indicating the changes in the fitting equations of various predictive models. Also, it was found that with an optimal dosage of 2%, the rejuvenator can significantly restore the basic performances of aged asphalt. Micromorphological analysis revealed that the surface of aged asphalt exhibited an uneven and groove-like structure, while the surface of recycled asphalt became shallower and more uniform. Four-component analysis showed that the proportion of light components in aged asphalt decreased, while the proportion of gel-like components increased. The addition of the rejuvenator effectively replenished the light oil components lost during aging. Additionally, there was a significant reduction of carbonyl and sulfoxide groups in aged asphalt. Molecular simulations revealed that the diffusion ability of light components in aged asphalt was weakened, while the Ar and S diffusion coefficients increased by 861.4% and 108%, respectively, indicating that the diffusion ability of these components was notably improved. Consequentially, the application of WEO as a rejuvenator in asphalt modification offers significant economic and environmental benefits.